The Political Economy of Economic Cooperation: The Case of Indonesia in Finding New Non-Traditional Markets - Pakpahan, Aknolt Kristian (Andalas Institute of International Studies UNAND, 2023)
Indonesia strives to achieve its goals of becoming a developed country by 2045 as stated in the Indonesia’s Dream 2015-2085, the most influential country in the Asia Pacific region, and to become a barometer of world economic growth. One of the strategies implemented by the Indonesian government to achieve those dreams is to open new economic cooperation in new non-traditional markets or countries that were not previously Indonesia's main trading partners. This research uses a national interest approach through descriptive research and a qualitative approach with data sources of literature studies from books, journals, and research reports that support the search for the analysis result. This study explains how the opening of new cooperation is carried out to achieve Indonesia's national interests, both economic interests to become a developed country by 2045 and political interests to affirm Indonesia's position within the framework of South-South cooperation. This research found that opening new economic cooperation can help Indonesia achieve its goal of becoming a developed country by 2045 and position Indonesia's political position as an important actor in promoting South-South cooperation.